Letter to the Editor - M Khazaei (JRI, 2010)
Dear Editor, The published article by Dr. Ai, et al. (1) on the secretion of vascular endothelial growth factor (VEGF) in a three-dimensional endometrial culture was of great surprise to me as this model had been earlier introduced by Fasciani, et al. (2) in 2003. This model was later developed by me (3, 4) and endometrial effects of different medications were evaluated in this model (5-7)...